Dirhodium-Catalyzed Chemo- and Site-Selective C–H Amidation of N,N-Dialkylanilines - Chen, Gong; Arai, Kenta; Morisaki, Kazuhiro; Kawabata, Takeo; Ueda, Yoshihiro (Synlett, 2021)
A method for dirhodium-catalyzed C(sp3)–H amidation of N,N-dimethylanilines was developed. Chemoselective C(sp3)–H amidation of N-methyl group proceeded exclusively in the presence of C(sp2)–H bonds of the electron-rich aromatic ring. Site-selective C(sp3)–H amidation proceeded exclusively at the N-methyl group of N-methyl-N-alkylaniline derivatives with secondary, tertiary, and benzylic C(sp3)–H bonds α to a nitrogen atom.
Keywords: C–H amidation; dirhodium complex; aniline; nitrene; site selectivity